GAMBARAN PERILAKU PENCEGAHAN COVID-19 PRE VAKSINASI I PADA MASYARAKAT DI RSUP H. ADAM MALIK - Enda Ertiyana; Novita Hasiani Simanjuntak; Janry Lewis H.S Sinaga (LPPM Universitas HKBP Nommensen, 2024)
Background: Coronavirus Disease 2019 (Covid-19) is an infectious disease of the respiratory tract caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) which is a new type of coronavirus that has never been previously identified in humans. One possible way to prevent the wider spread of the Covid-19 pandemic is by vaccination and it is still supported by the implementation of health protocols or behavior to wear masks, wash hands, keep distance, stay away from crowds and reduce mobility. Objective: This study aims to determine the description of preventive behavior before the first Covid-19 vaccination in the community at RSUP H. Adam Malik Methods: This research is a type of descriptive research. With the number of samples obtained 200 samples were assessed by distributing using a questionnaire. Results: As much 171 people (85.5%) had bad behavior in the act of keeping a distance, as many as 132 people (66%) had bad behavior in the act of wearing a mask, as many as 167 people (83.5%) had bad behavior in the act of washing hands, as many as 184 These people (92%) had bad behavior in the act of avoiding crowds, as many as 117 people (58.5%) had bad behavior on the act of reducing mobility. Conclusion: Based on the results of the research and discussion, a description of preventive behavior before the Covid-19 vaccination I in the community at H. Adam Malik Hospital showed that more than half of them behaved badly towards Covid-19 prevention behavior. Keywords: Covid-19, Covid-19 prevention behavior, Covid-19 vaccine